International financial sanctions: definition and historical evolution and the enlightenment on china’s major country diplomacy in the new ERA - Lei, Zhu; ., . (International Journal of Engineering and Technology, 2018)
Being a representative way of "smart sanctions", international financial sanctions have been increasingly adopted since the World War. This article, proceeding from the definition of international financial sanctions, sorts out its development stages and then discusses the rationality of its existence. It’s held in this article that the international financial sanctions based on multilateralism are reasonable to a certain degree for maintaining a sound global order. But given the asymmetric interdependence of the current international financial power, it is necessary to prevent financial sanctions from being taken advantage of by some major powers to interfere in other countries’ internal affairs. It’s suggested in the end of the article that on the one hand, China needs to take precautions in financial sanctions imposed by other countries; on the other hand, against the new era background of building a community of shared future for mankind and constructing a new model of international relations, China should change perceptions, take actions, and give full play to non-violent means such as financial sanctions so as to maintain its core national interests and global governance. Meanwhile, the sanction rules and system design should also be bettered.